Hydrogen production by Sulfurospirillum species enables syntrophic interactions of Epsilonproteobacteria. Issue 1 (December 2018) - Kruse, Stefan; Goris, Tobias; Westermann, Martin; Adrian, Lorenz; Diekert, Gabriele
Abstract Hydrogen-producing bacteria are of environmental importance, since hydrogen is a major electron donor for prokaryotes in anoxic ecosystems. Epsilonproteobacteria are currently considered to be hydrogen-oxidizing bacteria exclusively. Here, we report hydrogen production upon pyruvate fermentation for free-living Epsilonproteobacteria, Sulfurospirillum spp. The amount of hydrogen produced is different in two subgroups ofSulfurospirillum spp., represented byS. cavolei andS. multivorans . The former produces more hydrogen and excretes acetate as sole organic acid, while the latter additionally produces lactate and succinate. Hydrogen production can be assigned by differential proteomics to a hydrogenase (similar to hydrogenase 4 fromE. coli ) that is more abundant during fermentation. A syntrophic interaction is established betweenSulfurospirillum multivorans andMethanococcus voltae when cocultured with lactate as sole substrate, as the former cannot grow fermentatively on lactate alone and the latter relies on hydrogen for growth. This might hint to a yet unrecognized role of Epsilonproteobacteria as hydrogen producers in anoxic microbial communities. Epsilonproteobacteria, such asSulfurospirillum, can use molecular hydrogen as an electron donor for respiration. Here, the authors show thatSulfurospirillum can, in addition, release hydrogen during fermentation, allowing metabolic interactions with other hydrogen-consuming microorganisms.